Marked bodies: a corporeal history of colonial Australia - Haebich, Anna (Borderlands, 2008)
Western imaginings about marked ‘primitive’ bodies have a long history, yet studies of these practices have remained largely a-historical. Drawing on recent scholarship addressing the history and cultural meanings of the corporeal surface of the Western body this paper presents a preliminary historical analysis of the remaking of Indigenous corporeal surfaces and subjectivities under colonialism in Australia as part of the nineteenth century ‘civilising project’.